Z badań nad kulturą szkoły. W kalejdoskopie analiz i interpretacji - Nowosad, Inetta (Wydawnictwo Naukowe UAM, 2018)
The kaleidoscope category adopted in relation to school culture is meant to emphasise the diversity in the identificationof this scientificcategory. I refer to analyses of the definitionsof the term school culture as well as to research perspectives and attempts to specify the notion. As a result, some research areas identifying school culture have been recognised and theoretical and empirical perspectives of the understanding the specificityof school culture have been scrutinised from two separate perspectives. One of them is vertical and includes the history of educational research, in which school culture emerged at the interface of other scientificdisciplines. The other one, horizontal, focuses on the contemporary meaning of research and analyses of school culture in the area of educational studies.
History of Research on School Culture. In a Kaleidoscope of Analyses and Interpretations
Keywords: school culture; educational research; organizational culture